Database of processing techniques and processing factors compatible with the EFSA food classification and description system FoodEx2 related to pesticide residues Objective 2: Linking the processing techniques investigated in regulatory studies with the EFSA food classification and description system FoodEx2. Issue 11 (26th November 2018) - van Donkersgoed, Gerda; van den Boogaard, Coline; Graven, Coen; Koopman, Nynke; Mahieu, Karin; van der Velde‐Koerts, Trijntje; Herrmann, Michael; Kittelmann, Arno; von Schledorn, Maria; Scholz, Rebekka; Anagnostopoulos, Chris; Bempelou, Eleftheria; et al.
Abstract : In the framework of the project 'Database of processing techniques and processing factors compatible with the EFSA food classification and description system FoodEx2' a compendium of representative processing techniques was prepared as a result of Objective 1 . In Objective 2 the food / feed items and processes as described in the compendium of Objective 1 were coded using the FoodEx2 coding system. The coding covers the raw agricultural commodities and the food / feed items obtained after processing. Additionally a key facet was added in order to be able to link food and feed items to the EFSA RAC (Raw Agricultural Commodity)‐model. The RAC‐model links the food items as coded in the consumption data to raw agricultural commodities. Food items in this model are also coded using the FoodEx2 coding system. The sources used to code the foods, feeds and processes are described, as well as the coding decisions.